Transformation of intimacy among university students in a transitional social context in Tehran, Iran / Samane Etesami - Samane , Etesami (2017)
Making a desired intimate relationship is a challenging issue among young men and women in contemporary urban Iran. The current research examined how the couples’ intimacy in intimate relationships is related with the status of modern transformation of intimacy. This research aimed to examine how Giddens’s (1992) theory of transformation of intimacy would be applicable in the transitional urban context of Iran, viz. in Tehran. An online research design and a partially mixed methods approach was used in this study. The quantitative results derived from completed online questionnaires by 567 men and women showed a positive correlation between the level of an individual’s transformed attitude towards intimate relationships and gender roles and the level of women’s sexual agency. In addition, there was a positive correlation between the level of women’s sexual agency and the level of actual intimacy among partners. The combination of quantitative and qualitative results however, showed that the transformed intimacy has not been completely perceived or adhered to by individuals, rather a combination of transformed and stereotypical values were practiced by the respondents. The in-depth interviews amongst 37 male and female respondents revealed that men and women treated the transformation of intimacy selectively and based it on their own benefits. Theoretical dissection suggests that the incomplete process of transformed intimacy in the context of the study could be explained by three sources: first, the feminist perspective of the interrelatedness of the public and private domains in the society, and the prevalence of patriarchal discourse in personal relationships. Second: the condition of the transitional social context in which inconsistency between traditional values and new needs are dominant, and third: the existence of the market logic in intimate life. Accordingly, the theoretical discussion suggested that Giddens’s (1992) theory of transformation of intimacy is not totally applicable in a transitional social urban context of Iran, viz. in Tehran.